Investigating Feminist Utopia and Science Fiction through Ursula K. Le Guin's Ambiguous Utopia The Dispossessed (1974) - Oua,Fatima Zohra; Boumous,Moufida (Faculty of Letters and Foreign Languages Department of English, 2018)
During the few past decades, a good deal of attention has been paid to women’s position within society. The literary market has been fertilized with a considerable number of works by and about feminist utopia. With the aim of contributing to this field, this study analyzes Ursula K. Le Guin’s The Dispossessed (1974) based on utopian theories and feminist thoughts, besides the use of science fiction’s perspective. It explains, also, the role of people in changing their social conditions for the better. In three chapters, this study will delve into the deepest thoughts of the ambiguous anarchist utopia, to explore utopia’s real existence through spreading awareness among the individuals. Eventually, Le Guin proves the power of women in understanding and transcending the life’s complexities